2017
DOI: 10.1007/s10620-016-4312-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Bile Duct Injury After Percutaneous Thermal Ablation of Malignant Liver Tumors: A Retrospective Case–Control Study

Abstract: Bile duct injury after ablation of MLTs was the result of local treatment-related factors combined with the patients' general condition. The minimum safe distance for ablation of tumor abutting a bile duct was 10 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…It’s worth noting that the distance between the tumor and adjacent hilar bile ducts has highly important consequences on the therapeutic effect of RFA. Lin et al reported that a distance from the bile duct within 10 mm was thought to be a high-risk factor for ablation-related biliary complications for HCC nodules ( 30 ). RFA is still not recommended for application in HCC nodules adjacent to the HBDs in some clinical treatment guidelines of HCC ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It’s worth noting that the distance between the tumor and adjacent hilar bile ducts has highly important consequences on the therapeutic effect of RFA. Lin et al reported that a distance from the bile duct within 10 mm was thought to be a high-risk factor for ablation-related biliary complications for HCC nodules ( 30 ). RFA is still not recommended for application in HCC nodules adjacent to the HBDs in some clinical treatment guidelines of HCC ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…No local tumor progression was noted during the 29-month follow-up period. Previous studies have reported that the percutaneous thermal ablation of tumors close to the bile duct (within 10 mm) cause bile duct injury [12,13]. In one study [14], bile duct dilatation after RFA worsened prognosis as patients with severe dilatation in two or more bile duct segments showed lower survival and higher HCC recurrence than patients without this complication.…”
Section: Discussionmentioning
confidence: 98%
“…Tumor location should be considered for the successful and safe local ablation of HCCs. The management of periductal HCCs by RFA is challenging because thermal injury to the bile duct can result in biliary complications such as bile duct stricture and hepatic biloma [11][12][13]. In addition, central bile duct injury can severely impair liver function and lead to poor prognosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although some of the heat is removed by blood flow, the size of the affected area is still approximately 12–15 mm in diameter when 3 W of power is used for 10 min and is well demarcated, accurate and partly dependent on the duration of the illumination time. Heat injury to adjacent bile ducts is commonly encountered with thermal ablation because bile flow is slow and has a negligible cooling effect in contrast to blood flow, and it has been demonstrated to be associated with the distance between the tumor and bile duct . Nevertheless, bile duct damage with the PLA of tumors in the liver hilum is much lower than that reported with RFA and PEI because the laser light is rapidly decayed from the center to the periphery so that the possibility of thermo‐damage to adjacent critical structures would be reduced .…”
Section: Discussionmentioning
confidence: 99%